Diluting the founder effect: cryptic invasions expand a marine invader's range - Roman, Joe (The Royal Society, 2006)
Most invasion histories include an estimated arrival time, followed by range expansion. Yet, such linear progression may not tell the entire story. The European green crab (Carcinus maenas) was first recorded in the US in 1817, followed by an episodic expansion of range to the north. Its population has recently exploded in the Canadian Maritimes. Although it has been suggested that this northern expansion is the result of warming sea temperatures or cold-water adaptation, Canadian populations have higher genetic diversity than southern populations, indicating that multiple introductions have occurred in the Maritimes since the 1980s. These new genetic lineages, probably from the northern end of the green crab's native range in Europe, persist in areas that were once thought to be too cold for the original southern invasion front. It is well established that ballast water can contain a wide array of nonindigenous species. Ballast discharge can also deliver genetic variation on a level comparable to that of native populations. Such gene flow not only increases the likelihood of persistence of invasive species, but it can also rapidly expand the range of long-established nonindigenous species.